2002
DOI: 10.1046/j.1460-9568.2002.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral parieto‐frontal network for verbal working memory: an interference approach using repetitive transcranial magnetic stimulation (rTMS)

Abstract: Verbal working memory has been attributed to a left-dominant neuronal network, including parietal, temporal and prefrontal cortical areas. The current study was designed to evaluate the contribution of these brain regions to verbal working memory processes and to assess possible hemispheric asymmetry. The effect of repetitive transcranial stimulation (rTMS) on performance in a verbal working memory task both during, and after an rTMS train (110% of individual motor threshold, 4 Hz) over nine different scalp lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
5
38
0
Order By: Relevance
“…For example, delay-period activity during spatial delayed response (Brandt, Ploner, Meyer, Leistner, & Villringer, 1998;Pascual-Leone & Hallett, 1994) might be sensory, attentional, motoric, or some combination of these. The n-back task (Mottaghy, Gangitano, Krause, & Pascual-Leone, 2003;Mottaghy, Doring, Muller-Gartner, Topper, & Krause, 2002;Mottaghy et al, 2000) requires the simultaneous engagement of several retention-and control-related operations. The absence of laterality effect in our rTMS results is also consistent with the existing literature, which documents disruption of verbal working memory performance with right hemisphere as well as left hemisphere rTMS (e.g., Herwig et al, 2003;Mottaghy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, delay-period activity during spatial delayed response (Brandt, Ploner, Meyer, Leistner, & Villringer, 1998;Pascual-Leone & Hallett, 1994) might be sensory, attentional, motoric, or some combination of these. The n-back task (Mottaghy, Gangitano, Krause, & Pascual-Leone, 2003;Mottaghy, Doring, Muller-Gartner, Topper, & Krause, 2002;Mottaghy et al, 2000) requires the simultaneous engagement of several retention-and control-related operations. The absence of laterality effect in our rTMS results is also consistent with the existing literature, which documents disruption of verbal working memory performance with right hemisphere as well as left hemisphere rTMS (e.g., Herwig et al, 2003;Mottaghy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The n-back task (Mottaghy, Gangitano, Krause, & Pascual-Leone, 2003;Mottaghy, Doring, Muller-Gartner, Topper, & Krause, 2002;Mottaghy et al, 2000) requires the simultaneous engagement of several retention-and control-related operations. The absence of laterality effect in our rTMS results is also consistent with the existing literature, which documents disruption of verbal working memory performance with right hemisphere as well as left hemisphere rTMS (e.g., Herwig et al, 2003;Mottaghy et al, 2002). This may be because of the complex and distributed nature of the networks that support verbal working memory (e.g., Mottaghy et al, 2002Mottaghy et al, , 2003 and/ or that rTMS of a right hemisphere target is expected to have strong effects on the homologous contralateral region (Ferrarelli et al, 2004;Bestmann, Baudewig, Siebner, Rothwell, & Frahm, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a more complex design it would be possible to compare the effects of stimulating at different times during the delay, but increasing the duration of the pulse train at the frequency used here would not be possible without exceeding current safety guidelines ( Wassermann, 1998). Mottaghy et al (2002) applied TMS constantly at 4 Hz during the 30-sec performance block of a 2-back verbal WM task. As in the present study accuracy, but not RT, was the principal indicator of behavioral impairment related to prefrontal stimulation.…”
Section: Task Demandsmentioning
confidence: 99%
“…Studies of frontal lobe language functions have remained largely restricted to frontal regions outside Broca's area; these have demonstrated that TMS can be used to disrupt verbal working memory (WM) (Mottaghy et al, 2000;Mottaghy, Doring, Muller-Gartner, Topper, & Krause, 2002) and verb generation (Shapiro, Pascual-Leone, Mottaghy, Gangitano, & Caramazza, 2001). TMS studies attempting to reproduce some of the production deficits associated with Broca's aphasia have had limited success (Stewart, Walsh, Frith, & Rothwell, 2001;Flitman et al, 1998;Epstein et al, 1996Epstein et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Goldman-Rakic and others Goldman-Rakic, 2000;Levy and Goldman-Rakic, 2000;Mottaghy et al, 2002;Ungerleider et al, 1998] argue for what they call domain-specificity. Domain specificity reflects functional organization with regard to a certain class of stimuli or content, i.e., the domain (such as verbal or spatial in the case of working memory) independently of the required task or process.…”
Section: Introductionmentioning
confidence: 99%